Elucidating surface and bulk emission in 3D hybrid organic – inorganic lead bromide perovskites - Chi, Xiao (2020)
Three dimensional (3D) hybrid organic–inorganic lead halide perovskites (HOIP) have emerged in recent years as promising materials for a wide variety of optoelectronic applications. However, the photoluminescence energies in bromide‐based HOIP have been reported to vary in the range from 2.16 to 2.35 eV. The occurrence of surface reconstructions due to uncompensated surface ionic charges may change the photo‐physical properties of the surface regions, but this has not been studied in detail. Herein, by performing angle‐dependent photoluminescence (PL) and spectroscopic ellipsometry of single‐crystal as well as polycrystalline HOIP crystals, the intrinsic excitonic emissions from the surface and bulk regions are clearly identified. It is verified that the high energy PL at 2.31 eV originates from a phase‐modified surface region. The large absorption coefficient of perovskite results in signal depletion of the lower energy PL at 2.16 eV, which originates from the bulk. High resolution synchrotron X‐ray diffraction reveals that air‐exposed HOIP crystals form a multilayer structure consisting of PbBr2, and an interfacial layer of orthorhombic phase, while the bulk crystal remains cubic phase. This study provides the unambiguous identification of a phase‐modified surface region with a larger band gap than the bulk and which dominates the excitonic emission in HOIP crystals.